INTEGRITI DALAM PERKHIDMATAN AWAM PADA ERA TUNKU ABDUL RAHMAN PUTRA AL-HAJ, 1957-1970 - Veerasamy, Loganathan; Raja, Sivachandralingam Sundara (SEJARAH: Journal of the Department of History, 2017)
The efficient administration of any country depends on government officials of high integrity. Integrity as a concept combines rectitude of conduct, purity of motive, moderation and balance in dealing with issues as well as transparency. Integrity is relevant in the life of a nation as it is in the daily life of an individual. Malaysia’s success in this respect is attributable to leaders and officials of high integrity who have been administering and leading the nation through difficult times from the pre-independence era until present times. In this context, it is significant to emphasise the role played by Tunku Abdul Rahman, the first Prime Minister of the Federation of Malaya in laying the foundation of a civil service that upholds integrity. This is reflected in the selective appointment of civil servants whose sense of integrity helps to build a positive image of the nation. Tunku had indeed contributed greatly towards forging a model civil service.